2011
DOI: 10.5480/1536-5026-32.4.234
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment and Job Satisfaction in Associate Degree Nurse Educators

Abstract: The purpose of this study was to examine empowerment, job satisfaction levels, and relationships among 139 associate degree nursing educators.The Conditions of Work Effectiveness II, Psychological Empowerment Scale, and Job Diagnostic Survey were used. Findings indicated that the majority of educators were satisfied with their jobs as nursing faculty and felt empowered in their workplaces. Psychological empowerment demonstrated the strongest positive correlation with job satisfaction. There were no significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 13 publications
2
30
0
Order By: Relevance
“…In a study with CWEQ-II, whose objective was to evaluate the management capacity of a group of managing and practical nurses, the Cronbach's Alpha was 0.91 (16) ; in another one, authors examined the relation between the perception of 257 nurses of critical areas among empowerment by means of CWEQ-II and the Anticipated Turnover Scale, the result of the Alpha was 0.82 (17) ; on empowerment and satisfaction of teaching nurses, the alpha was 0.84 (18) . Such results indicate lower values than the obtained ones in this research.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with CWEQ-II, whose objective was to evaluate the management capacity of a group of managing and practical nurses, the Cronbach's Alpha was 0.91 (16) ; in another one, authors examined the relation between the perception of 257 nurses of critical areas among empowerment by means of CWEQ-II and the Anticipated Turnover Scale, the result of the Alpha was 0.82 (17) ; on empowerment and satisfaction of teaching nurses, the alpha was 0.84 (18) . Such results indicate lower values than the obtained ones in this research.…”
Section: Discussionmentioning
confidence: 99%
“…The mentoring of newly hired professors will become a critical issue for administrators in an increasingly competitive environment and for educators seeking supportive environments to facilitate their successful integration as scholars. Literature exists on organizational culture (Cameron & Quinn, 1999;Johnson, 2009;Tourangeau et al, 2012), psychological empowerment (Baker, Fitzpatrick, & Griffin, 2009;Spreitzer, 1995;Thomas & Velthouse, cited in Spreitzer, 1995, p. 1443, and structural empowerment (Hebenstreit, 2012). Less is known about the overarching question for our study about how organizational culture and the perceived level of psychological and structural empowerment associated with one's work environment impact nursing faculty (Singh, Pilkington, & Patrick, 2014).…”
Section: Introductionmentioning
confidence: 92%
“…[40,41] However, it is also acknowledged that for some CIs it may take years of experience to develop confidence. [40] Over the years, evidence from research in nursing education has demonstrated that these qualities are important in clinical teaching. As such the CI characteristics identified in this study and previous studies could be considered during ongoing professional development workshops and training of CIs to maximise students clinical learning experiences.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Other authors suggest that some CIs disappear or detach away from the clinical setting because of their incompetence [36] and lack of confidence. [40] CIs need confidence to accomplish their role effectively. [40,41] However, it is also acknowledged that for some CIs it may take years of experience to develop confidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation